Theory Behind Formation of Neutrino and Procedure of Calculating Mass of Neutrino Under Various Circumstances - Dhage, Gaurav Sahebrao (JOURNAL OF ADVANCES IN PHYSICS, 2017)
Study of neutrino is very important aspect of particle physics. Neutrino has unique characteristics like zero charge and negligible mass compared to other subatomic particles which makes extremely difficult to analyse and to study behaviour of Neutrino; through experimental studies. So Neutrino is still unknown territory for humankind. Understanding how neutrinos operate is essential for next steps in new physics. As it is difficult to study them experimentally; I am using theoretical approach in this research paper to study Neutrino. In this research paper I have expressed my thoughts and proposed hypothesis. Based on hypothesis I have derived formula for calculation of Neutrinos mass. In this paper I have also observed some properties Neutrino based on my hypothesis.